2018
DOI: 10.1177/1747021818791994
|View full text |Cite
|
Sign up to set email alerts
|

Working memory in older adults declines with age, but is modulated by sex and education

Abstract: Working memory (WM), which underlies the temporary storage and manipulation of information, is critical for multiple aspects of cognition and everyday life. Nevertheless, research examining WM specifically in older adults remains limited, despite the global rapid increase in human life expectancy. We examined WM in a large sample ( N = 754) of healthy older adults (aged 58-89) in a non-Western population (Chinese speakers) in Taiwan, on a digit n-back task. We tested not only the influence of age itself and of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
37
1
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(52 citation statements)
references
References 132 publications
(209 reference statements)
12
37
1
2
Order By: Relevance
“…Indeed, overall cognitive function measures (e.g., MMSE) are routinely used in clinics and research for cognitive [79][80][81] and low scores in these tests are associated with numerous negative health-related outcomes, such as insomnia, loneliness, and dementia [82][83][84][85]. Improvements in short-term memory may have a direct impact on an individual's quality of life, given its close association with various aspects of cognition and every-day activities, such as conversation, reading, learning, mathematics [6,7]. In addition, reduced short-term memory is commonly found in people with AD [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, overall cognitive function measures (e.g., MMSE) are routinely used in clinics and research for cognitive [79][80][81] and low scores in these tests are associated with numerous negative health-related outcomes, such as insomnia, loneliness, and dementia [82][83][84][85]. Improvements in short-term memory may have a direct impact on an individual's quality of life, given its close association with various aspects of cognition and every-day activities, such as conversation, reading, learning, mathematics [6,7]. In addition, reduced short-term memory is commonly found in people with AD [8].…”
Section: Discussionmentioning
confidence: 99%
“…Among the cognitive domains affected by aging, short-term memory and dual-task performance have gained widespread attention owing to their relevance to the individual's autonomy. In fact, short-term memory -the capacity of holding an amount of information for a short period of time [6] -is involved in various aspects of cognition (e.g., executive function) and every-day activities, such as conversation, reading, learning, mathematics [6,7]. Furthermore, a progressive decline in this cognitive domain is commonly found in AD patients [8].…”
Section: Introductionmentioning
confidence: 99%
“…The samples compared here were of similar age and had a similar educational level (undergraduates) and in Datasets I and II, a similar distribution of gender. While Dataset III only consisted of data collected from females, a recent study by Pliatsikas et al ( 2019 ) demonstrated that gender, age, and education level affect response accuracy after a single N-Back training session in healthy older individuals. Since the present study consists of N-Back performance across 1 or 2 sessions in young subjects, we do expect these variables to have a moderate effect on behavioral and electrophysiological results.…”
Section: Discussionmentioning
confidence: 99%
“…SEBAS participants completed 1-back and 2-back tasks. Further details of the N-back task are available in [ 40 ].…”
Section: Methodsmentioning
confidence: 99%